Perspectives of Co-Operation between the Baltic Countries and the Eurasian Economic Union Member States in the Context of Eurasian Integration Process - Yana Glittova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The purpose of the article is to analyse the perspectives of co-operation between the Baltic countries and the Eurasian Economic Union member states. To conduct study and draw conclusions as a research method were applied situational analysis. During analysis were identified the following elements-events of recent years associated with the: imposing of economic sanctions against Russia, creating of Eurasian Economic Union (EAEU), China’s Silk Road Economic Belt Initiative, NATO activities connected with the increasing major exercises conducted by Alliance on the borders of the EAEU member states, policies of the Baltic states. The object of the study is the relations between the EAEU member states and the Baltic countries.The subject of the study is the political and economic aspects of the EU, Eurasian integration and the Silk Road Economic Belt. Dependent variables used in the research: the official position of the EAEU, the official position of the EU, Silk Road Economic Belt, trade and economic interaction, the regime of economic sanctions, normalisation of ties between Russia and the EU, territorial aspect, infrastructure, bilateral legal framework. Independent variable used in the research: NATO. It is analysed the crucial role of intensifying relations between the Russian Federation and the European Union in creating favorable conditions for the restoring relations between the Baltic countries and the Eurasian Economic Union member states, as well as strenghten relations between European Union and Eurasian Economic Union. It is noted that the relations between the European Union and Russia are not interrupted, trade and economic co-operation continues, but at a lower level. It is analysed relations between Baltic states and EAEU member states, including economic interaction and the legal basis. It is highlited the importance of full restoration of economic and trade ties.One of the key issues of the article is that the integration processes in the Eurasian space have activated the process of implementation which is dynamically developing within EAEU. It is stressed that the formation of transport corridors in the territory of the EAEU member states is one of the key tasks within the conjunction of the EAEU and Silk Road Economic Belt. It is noted that to activate these projects, a legal framework of bilateral basis is needed — bewteen China and countriesparticipants of the EAEU. It is stressed that China is interested in co-operation with the EU within the Silk Road Economic Belt. It is shown that the strategic vector of the Baltic states, as well as the EU, the EAEU and the Belt and Road initiative, is economic. The intensification of relations and the strengthening of economic ties between the EU and the EAEU is possible after the lifting of mutual sanctions. It is noted military activity of NATO at the border zones of the Baltic countries with the Russia and Belarus as a negative factor affecting the relations.